2021
DOI: 10.3389/fgene.2021.585058
|View full text |Cite
|
Sign up to set email alerts
|

In silico Identification of 10 Hub Genes and an miRNA–mRNA Regulatory Network in Acute Kawasaki Disease

Abstract: Kawasaki disease (KD) causes acute systemic vasculitis and has unknown etiology. Since the acute stage of KD is the most relevant, the aim of the present study was to identify hub genes in acute KD by bioinformatics analysis. We also aimed at constructing microRNA (miRNA)–messenger RNA (mRNA) regulatory networks associated with acute KD based on previously identified differentially expressed miRNAs (DE-miRNAs). DE-mRNAs in acute KD patients were screened using the mRNA expression profile data of GSE18606 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Therefore, several steps were performed to identify these key dysregulated genes, including identification of intramodular hub genes in the non-preserved modules, integration of co-expressed hub genes with PPI networks, and identification of the hub-central genes in the bTB-specific co-expressed hub genes-based PPI networks through MCC topological algorithm. Noteworthy, in parallel with the current study, the MCC algorithm has been used as an objective criterion for measuring node centrality and identifying important genes/proteins in candidate networks in disease-based system biology studies ( Bai et al, 2020 ; Yang et al, 2020 ; Ma et al, 2021 ; Wang Y. et al, 2021 ). Finally, a total of 260 hub-central genes were found in the 7 bTB-specific non-preserved modules that these genes were hubs in their co-expression networks and also played a central role in the respective co-expressed hub genes-based PPI networks (so-called double centrality) which were as critical targets in related to the promotion of the bTB establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several steps were performed to identify these key dysregulated genes, including identification of intramodular hub genes in the non-preserved modules, integration of co-expressed hub genes with PPI networks, and identification of the hub-central genes in the bTB-specific co-expressed hub genes-based PPI networks through MCC topological algorithm. Noteworthy, in parallel with the current study, the MCC algorithm has been used as an objective criterion for measuring node centrality and identifying important genes/proteins in candidate networks in disease-based system biology studies ( Bai et al, 2020 ; Yang et al, 2020 ; Ma et al, 2021 ; Wang Y. et al, 2021 ). Finally, a total of 260 hub-central genes were found in the 7 bTB-specific non-preserved modules that these genes were hubs in their co-expression networks and also played a central role in the respective co-expressed hub genes-based PPI networks (so-called double centrality) which were as critical targets in related to the promotion of the bTB establishment.…”
Section: Discussionmentioning
confidence: 99%
“…PPI analysis showed that three hypomethylated, high expression hub genes were CD177, IL1RN, and MYL9. CD177 is a neutrophil surface molecule, many studies have proved that there is a close relationship between CD177 and KD [ 33 , 34 , 35 ]. Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, hsa-miR-4443 (miRbase accession MI0016786, http://www.mirbase.org/cgibin/mirna_entry.pl?acc=MI0016786 ) was the only 1 co-differently expressed microRNA identified in this study. Hsa-miR-4443 was reported to be involved in several types of cancer and in the biology of the immune system, such as participating in the malignancy of breast cancer [ 36 , 37 ], tumors of glial origin [ 38 , 39 ] and head and neck squamous cell carcinoma [ 40 ], suppressing invasiveness of ovarian cancer [ 41 ] and colon cancer [ 42 ], promoting the resistance of non-small cell lung cancer cells to epirubicin [ 43 , 44 ], downregulated in hepatocellular carcinoma [ 45 ] peripheral blood mononuclear cells of non-segmental vitiligo (NSV) patients [ 46 ] and acute Kawasaki disease [ 47 , 48 ], and regulating T cell-mediated inflammatory processes [ 49 ] and monocyte activation [ 50 ]. Although no studies on the roles of hsa-miR-4443 in neurodegenerative diseases have been reported yet, the effects of hsa-miR-4443 on tumors of glial origin [ 38 , 39 ] and immune cells [ 49 , 50 ] indicated hsa-miR-4443 regulating glial cells and neuroimmunity to participate in occurrence of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%